Characterization of a Spring Wheat Association Mapping Panel for Root Traits. (1st September 2014) - Narayanan, Sruthi; Vara Prasad, P. V.
Abstract : Improved root traits are important for increased nutrient and water uptake and productivity in wheat ( Triticum spp.). The objectives of this research were to characterize genetic variability for root traits in a Spring Wheat Association Mapping (AM) Panel and determine whether root traits are related to shoot dry weight, tiller number, and plant height. Rooting depth, root dry weight, root/shoot ratio, and shoot traits were determined for 250 genotypes of the AM panel. The remaining root traits were measured for a subset of 30 genotypes selected based on rooting depth. Significant genetic variability was observed for root traits. Genotypes Treasure and IDO686 were ranked high and genotypes MN08106‐6 and MT1016 were ranked low for most root traits in the AM panel or its subset. Shoot dry weight had positive relationships (correlation coefficient, r ≥ 0.50) with rooting depth and root dry weight in the AM panel, and with total root length, total root surface area, root length density (30–60‐cm soil depth), fine root length, and fine root surface area in the subset. Tiller number also had positive relationships ( r ≥ 0.50) with all the above root traits except rooting depth and root dry weight. Plant height had no correlations with most root traits. Plant height had only weak negative relationships (|r| ≤ 0.36) with root dry weight and root/shoot ratio in the AM panel. The genetic variability identified in this research for root traits offers useful information for wheat improvement programs for choosing genotypes with contrasting root characteristics.